Sasaran dan strategi Dakwah Nagari - Awis Karni (Universitas Islam Negeri Imam Bonjol Padang, 2004)
The target of dakwah is in society, that why the analysis weared sociology. We need to know how picture aboutMinangkabau village( that call nagari) society now. Later, after earning pictuæ about Minangkabau nagari society, we can apply dakwah strategy to the nagari society.The writer tries to analyze the change of nagari society at present, and what to do with dakwah strategy in nagari development.